Day 1 Tue, March 13, 2018 2018
DOI: 10.2118/189800-ms
|View full text |Cite
|
Sign up to set email alerts
|

A Laboratory Study of CO2 Interactions Within Shale and Tight Sand Cores - Duvernay, Montney and Wolfcamp Formations

Abstract: The most commonly used technology for development of unconventional reservoirs is horizontal wells combined with large multi-stage hydraulic fracture treatments. However, even with these technological advancements, primary recovery factors are generally less than 10 percent of the hydrocarbon in place. Water is currently the primary fracturing fluid used in most commercial developments. There is growing interest in non-aqueous (e.g. CO2) fluid systems not only to reduce water usage, but to increase well produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Dissolution of organic content by CO 2 can increase permeability. Reynolds et al showed that in cases where the core samples contained high levels of organic matter, permeability increased after soaking in pressurized CO 2 . Adsorption of CO 2 in shale can decrease permeability.…”
Section: Laboratory Experiments Related To High-pressure Gas Eor In Ulrsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dissolution of organic content by CO 2 can increase permeability. Reynolds et al showed that in cases where the core samples contained high levels of organic matter, permeability increased after soaking in pressurized CO 2 . Adsorption of CO 2 in shale can decrease permeability.…”
Section: Laboratory Experiments Related To High-pressure Gas Eor In Ulrsmentioning
confidence: 99%
“…Reynolds et al showed that in cases where the core samples contained high levels of organic matter, permeability increased after soaking in pressurized CO 2 . 167 Adsorption of CO 2 in shale can decrease permeability. Al Ismail et al 104,168 studied the effect of CO 2 adsorption on Utica and Permian Shale samples.…”
Section: Laboratory Experiments Related To High-pressure Gas Eor In Ulrsmentioning
confidence: 99%
“…The associated goals of reducing greenhouse gas emissions and increasing oil recoveries have led to growing interest in injecting CO 2 and/or produced rich gas hydrocarbons for both gas storage and enhanced oil recovery (EOR). ,, This interest has resulted in several recent pilot-scale injections of CO 2 and rich gas hydrocarbons into the Bakken, ,,, but experimental data needed to support successful field projects that compare these gases’ abilities to mobilize crude oil under relevant reservoir conditions are limited. Recently, CO 2 and various hydrocarbon gas minimum miscibility pressures (MMPs) were measured with crude oils produced from the Three Forks (TFs) and Middle Bakken (MB) intervals of the Bakken Petroleum System.…”
Section: Introductionmentioning
confidence: 99%
“…The success of miscible and immiscible CO 2 floods in conventional reservoirs, as well as the desire to store CO 2 , has led several authors to suggest its use for enhanced oil recovery (EOR) in tight oil plays including the Bakken Petroleum System based on experimental work and simulations. However, it is likely that the CO 2 flow patterns through the reservoir rock as occurs in conventional (i.e., permeable) reservoirs are not representative of the fracture-dominated flow that controls how injected EOR fluids move through tight hydraulically fractured systems like the Bakken Petroleum System. ,,, Thus, CO 2 injected into the Bakken Petroleum System is not likely to flow primarily through the rock matrix, as it does in a conventional reservoir flood but rather will flow primarily through the fractures as driven by the pressure gradient and around the rock matrix via the induced (or natural) fractures. Once the pressure gradient is reduced in the fractures, the bulk rock matrix holding the unproduced oil experiences a “bath” of CO 2 , where the CO 2 permeates by diffusion into the rock matrix and oil hydrocarbons diffuse out of the rock matrix into the bulk CO 2 in the fractures.…”
Section: Introductionmentioning
confidence: 99%